2020
DOI: 10.1007/s42773-020-00060-4
|View full text |Cite
|
Sign up to set email alerts
|

Sorption and degradation of imidacloprid and clothianidin in Chinese paddy soil and red soil amended with biochars

Abstract: Application of biochar technology in the remediation of organic contaminated soils has drawn growing interest in recent years. In this study, sorption and degradation of two typical neonicotinoid insecticides, imidacloprid (IMI) and clothianidin (CLO) in Chinese typical paddy soil and red soil amended with six kinds of biochars were investigated. The results showed that surface area (SA), pH, total organic carbon and dissolved organic carbon (DOC) of the two soils all increased after biochar amendment, while H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…However, the half-life of THI in the soil increased from 89.4 to 120 days, suggesting that BC450 elevated the persistence of soil THI. Zhang et al (2020d) examined the adsorption and degradation of two representative neonicotinoid insecticides in typical Chinese paddy soil and red soil by six types of biochars. The results indicated that the pH value, total organic carbon, dissolved organic carbon, and surface area of each soil type exhibited an increase following biochar amendment, while H/C reduced.…”
Section: Organic Pollutantsmentioning
confidence: 99%
“…However, the half-life of THI in the soil increased from 89.4 to 120 days, suggesting that BC450 elevated the persistence of soil THI. Zhang et al (2020d) examined the adsorption and degradation of two representative neonicotinoid insecticides in typical Chinese paddy soil and red soil by six types of biochars. The results indicated that the pH value, total organic carbon, dissolved organic carbon, and surface area of each soil type exhibited an increase following biochar amendment, while H/C reduced.…”
Section: Organic Pollutantsmentioning
confidence: 99%
“…Degrading rate of clothianidin in consortia treatment was much higher than that of natural attenuation and biostimulation, which transforms nitroimino moiety of clothianidin to urea compound by cleavage of different bonds (Wang et al, 2019). Recently, Zhang et al (2020) found that degradation of clothianidin in soil may be associated with biotic and abiotic processes. More specifically, the microbial degradation of neonicotinoids could be greatly influenced by the concentration of insecticides, soil temperature, moisture content, and microorganism adaptability (Pietrzak et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The low pyrolysis temperature favours the biodegradation of pesticide due to the availability of N‐atoms to microorganisms while the high pyrolysis temperature favours the chemical degradation of imidacloprid due to the formation of reactive oxygen species. Among the various kinds of biochar utilized, the best degradation results were found for pig manure biochar at a pyrolysis temperature of 700 °C [56] …”
Section: Approaches For the Elimination/degradation Of Imidaclopridmentioning
confidence: 99%
“…Among the various kinds of biochar utilized, the best degradation results were found for pig manure biochar at a pyrolysis temperature of 700 °C. [56] Voorhees et al, investigated a laboratory bench scale experiment for the imidacloprid removal. For the experimental setup activated carbon, Aquacarb® NS, a reactivated coal/ coconut shell charcoal and biochar derived from organic sustainably grown yellow pine wood which was pyrolyzed at 900 °C was utilized.…”
Section: Adsorptionmentioning
confidence: 99%